Bullying and cyberbullying is associated with low levels of cognitive and metacognitive learning strategies in young people - Solas-Martínez, Jose Luis; De la Torre-Cruz, Manuel J.; Rusillo-Magdaleno, Alba; Martínez-López, Emilio J. (Frontiers in Psychology, 2025)
This study analyzed the relationship between bullying and cyberbullying, both as victims and aggressors, and the use of cognitive and metacognitive learning strategies in adolescents aged 10 to 16. A total of 1,330 Spanish students participated (48.95% boys), with an average age of 13.22 years. The Motivated Strategies for Learning Questionnaire (MSLQ) was used to assess five key learning strategies: rehearsal, elaboration, organization, critical thinking, and metacognitive self-regulation. The European Bullying Intervention Project Questionnaire (EBIP-Q) and the European Cyberbullying Intervention Project Questionnaire (ECIP-Q) were applied to evaluate levels of bullying and cyberbullying. The association between variables was analyzed through analysis of covariance (ANCOVA) and binary logistic regression analysis. The findings revealed a statistically significant negative association between bullying (traditional and cyberbullying) and the use of learning strategies for both victims and aggressors. Girls were more affected, particularly in cases of cyberbullying, where they showed lower scores in rehearsal, elaboration, and metacognitive self-regulation. In contrast, boys who were bullying aggressors scored higher in critical thinking. The risk of less frequent use of learning strategies among victims increased by 1.3 times for bullying and 2 times for cyberbullying. Similarly, this risk for aggressors rose by 1.4 times for boys and 1.8 times for girls in cases of bullying, and by 2.5 times for both genders in cases of cyberbullying. The study suggests implementing specific and cooperative actions involving students, teachers, and families to strengthen the proper use of learning strategies among victims and aggressors, especially in girls involved in cyberbullying episodes.